026 Left bundle branch block as an activation criterion for primary percutaneous coronary intervention: where is the evidence?. (16th May 2012) - Brown, A J; Malone-Lee, M; McCormick, L M; Hoole, S P; Schofield, P M; West, N E J
Abstract : Background: The activation criteria for primary percutaneous coronary intervention (PPCI) includes chest pain in association with either ST-segment elevation (STEMI) or new-onset left bundle branch block (LBBB) on the ECG. However, defining LBBB as new is challenging acutely and the poor specificity of indeterminate chronicity LBBB may result in unnecessary PPCI activations. Published data are conflicting with regard to the utility of LBBB as a triage criterion for PPCI and subsequent outcomes are undefined. Methods: Consecutive patients attending a single UK tertiary centre for presumed PPCI between September 2008 and December 2010 were included (n=1328). The activation ECG was obtained from the hospital PPCI database, as were demographic data. Outcome data were obtained from notes and national databases. MACE was defined as a composite of mortality and unplanned revascularisation. Two interventionists blinded to patient outcome reviewed the angiographic images and adjudicated if the activation was appropriate. Results: Chest pain with LBBB (LBBB-activation) occurred in 88 patients (6.6%) of the PPCI cohort. Comparing LBBB-activations to those with STEMI demonstrated that LBBB-activations were older (mean age 70.3±12.4 vs 64.6±13.4 years; p<0.001) and less likely to be male (67.0% vs 76.8%; p=0.004). Otherwise, baseline demographics were similar. Eighteen (20.5%) patients with LBBB had an acute thrombotic coronary occlusion confirmed at angiography and received PPCI. The final adjudicated diagnoses for LBBB-activations were acute coronary syndrome (ACS) (39.8%), non-ACS cardiac (28.4%) and non-cardiac (31.8%). A history of previous MI (p=0.002) and presence of cardiogenic shock on arrival (p=0.04) were more prevalent in the appropriate LBBB-activations. One-year mortality and MACE were higher for appropriate LBBB-activations than the STEMI activations (27.8% vs 7.9%; p=0.002 (Abstract 026 figure 1 ) and 33.3% vs 9.1%; p<0.001 respectively). Conclusions: Less than half of LBBB-activations had an ACS and, of these, only half had a thrombotic coronary occlusion requiring PPCI. However, LBBB-activations have a significantly worse prognosis and merit urgent referral. Enhanced triage methods are required to correctly identify acute MI requiring PPCI in those with LBBB.